What the Public Think about Social Services: A Report from Scotland. (5th September 2019) - McCulloch, Trish; Webb, Stephen
Abstract: This article reports on findings of a government-funded research project which set out to understand what the public think about social services in Scotland. The authors were particularly keen to examine issues of legitimacy, trust and licence to operate for social services as they are framed in public perceptions. Drawing on a national online survey of 2, 505 nationally representative adults, the findings provide the first and largest empirical data set on public perceptions of social services in Scotland. Data analysis occurred in two stages and employed descriptive statistical measurement and cross-tabulation analysis. The findings indicate that, overall, people in Scotland are positive about social services and the value of their impact on society. Furthermore, they believe that social services perform a valuable public role. These findings are significant for debates surrounding social services and suggest that the Scottish public has a more positive view of social services than social service workers and welfare institutions typically perceive. The findings demonstrate the need to develop a more theoretically rich understanding of the relationships between public perception, legitimacy and social licence in social services, including attention to co-productive models of engagement.